Exploring Students’ Perceptions of Peer Collaboration in Developing English Speaking Skills at SMP N 18 Medan - Ardima Trojesi Govian Hasugian; Ray Valentino Purba; Yolanda Novita Silaban; Kartina Rahmadhani Rambe (English Lecturers and Teachers Association (ELTA), 2026)
This study examined eighth-grade students’ perceptions of peer collaboration as a strategy for developing English-language skills at SMP Negeri 18 in Medan, Indonesia. A descriptive qualitative design was employed, involving 29 students. Eight participants were purposively selected for semi-structured interviews, and a perception-based questionnaire was distributed to the entire group. Interview data were analyzed thematically using Braun and Clarke’s six-phase framework. The findings revealed that the usefulness of peer feedback was the highest-rated dimension (84.4%), followed by communicative confidence (81.3%), speaking anxiety reduction (78.1%), and motivation to communicate (75.0%). Critically, these findings indicated that peer collaboration substantially diminished affective barriers, particularly speaking anxiety, which commonly hinder EFL oral development, while concurrently enhancing learners’ communicative repertoire through informal, non-evaluative peer interactions. The study made a distinctive contribution by focusing on junior secondary EFL learners in an Indonesian urban context, a population largely absent from existing peer collaboration research, and by integrating both affective and linguistic dimensions within a single qualitative inquiry. Practically, the findings provide evidence-based guidance for EFL teachers and curriculum designers to embed structured collaborative speaking tasks into junior secondary instruction. These insights advance understanding of how peer-mediated learning can be leveraged to foster oral communicative competence in contexts where teacher-centered approaches have historically dominated. Keywords : peer collaboration; English speaking skills; EFL learners; speaking anxiety